2011
DOI: 10.1177/0265532211413444
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the revised TOEIC® test: A multiple-sample analysis

Abstract: This study examined the factor structure of the listening and reading sections of the revised Test of English for International Communication (TOEIC ® ) test. The data from the TOEIC IP (institutional program) test taken by 569 English learners were randomly split into two samples (n = 285 vs. 284). Four models (higher-order, correlated, uncorrelated, and unitary) were hypothesized on the basis of the literature and were tested with each sample. The results from confirmatory factor analysis suggested that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…In one study, researchers administered the Test of English for International Communication (TOEIC) to 12,000 examinees in Taiwan, Korea, and Japan and found a significant and strong correlation ( r = 0.76) between their reading comprehension and listening comprehension skills (Liao, Qu, & Morgan, 2010; reported in Tschirner, , p. 204). In another study with Asian English learners using the revised TOEIC, In'nami and Koizumi () also found a strong and significant relationship ( r = 0.87) between students’ reading comprehension and listening comprehension proficiency (Tschirner, , p. 204). Likewise, Bozorgian () examined Iranian students' scores on the International English Language Testing System and found that the strongest correlations among language skills were between listening and reading proficiency ( r = 0.74; Tschirner, , p. 205).…”
Section: Literature Reviewmentioning
confidence: 91%
“…In one study, researchers administered the Test of English for International Communication (TOEIC) to 12,000 examinees in Taiwan, Korea, and Japan and found a significant and strong correlation ( r = 0.76) between their reading comprehension and listening comprehension skills (Liao, Qu, & Morgan, 2010; reported in Tschirner, , p. 204). In another study with Asian English learners using the revised TOEIC, In'nami and Koizumi () also found a strong and significant relationship ( r = 0.87) between students’ reading comprehension and listening comprehension proficiency (Tschirner, , p. 204). Likewise, Bozorgian () examined Iranian students' scores on the International English Language Testing System and found that the strongest correlations among language skills were between listening and reading proficiency ( r = 0.74; Tschirner, , p. 205).…”
Section: Literature Reviewmentioning
confidence: 91%
“…They found a significant and high correlation between listening and reading ( r = 0.76) as well as significant and moderate relationships between listening and speaking ( r = 0.66), reading and writing ( r = 0.61), and speaking and writing ( r = 0.62) (p. 13.4). In'nami and Koizumi () found an even higher correlation ( r = 0.87) between the listening and reading sections on the revised TOEIC 2006 for 569 Asian English learners (p. 145).…”
Section: Review Of Literaturementioning
confidence: 96%
“…In one study, researchers administered the Test of English for International Communication (TOEIC) to 12,000 examinees in Taiwan, Korea, and Japan and found a significant and strong correlation ( r = .76) between their reading comprehension and listening comprehension skills (Liao, Qu, & Morgan, ). In another study with Asian English learners using the revised TOEIC, In'nami and Koizumi () also found a strong and significant relationship ( r = .87) between students’ reading comprehension and listening comprehension proficiency. Likewise, Bozorgian () examined Iranian students’ scores on the International English Language Testing System and found that the strongest correlations among language skills were between listening comprehension and reading comprehension proficiency ( r = .74).…”
Section: The Relationship Between Reading Comprehension and Listeningmentioning
confidence: 90%